Alcohol-related mortality following self-harm: a multicentre cohort study. (8th July 2014) - Bergen, Helen; Hawton, Keith; Webb, Roger; Cooper, Jayne; Steeg, Sarah; Haigh, Matthew; Ness, Jennifer; Waters, Keith; Kapur, Navneet
Objectives: To assess alcohol-related premature death in people who self-harm compared to the general population, including variation by socioeconomic deprivation. Design: A retrospective longitudinal cohort analysis from the Multicentre Study of self-harm in England, 1 January 2000 to 31 December 2010, with cause-specific mortality follow-up through to 31 December 2012. Setting: Six emergency departments in Oxford, Manchester and Derby. Participants: All individuals aged 15 years or more who presented with self-harm ( n = 39, 014) to general hospital emergency departments, together with follow-up mortality information from the Data Linkage Service of the Health and Social Care Information Centre. Main outcome measures: Standardised mortality ratios (observed/expected number of deaths: SMRs) and mean number of years of life lost (YLL) were estimated for alcohol-related mortality. Patients' characteristics and clinical management following self-harm were also examined. Results: After 7.5 years' (median) follow-up, 2695 individuals (6.9%) had died, significantly more males (9.5%) than females (5.0%), including 307 (11.4%) from alcohol-related causes. Alcohol-related death was more frequent than expected in both males (SMR 8.5, 95% CI 7.3 to 9.8) and females (11.6, 9.8 to 13.7), equating to 33.7 YLL (95% CI 32.4 to 35.0) in males and 38.1 YLL (36.6 to 39.6) in females. It was not associated with area-level socioeconomic deprivation. Alcohol-related death was associated with unemployed/sick/disabled status, alcohol use during self-harm, referral to drug/alcohol services and lack of psychosocial assessment following self-harm. Conclusions: Hospital-presenting self-harm patients should receive assessment following self-ham according to national guidance to enable early identification and treatment of alcohol problems.